Photomagnonic nanocavities for strong light-spin wave interaction - P.A. Pantazopoulos; N. Stefanou; E. Almpanis; N. Papanikolaou (Physical Review B, 2017)
The interaction of visible and near-infrared light with spin waves in appropriately designed dual nanocavities, for both photons and magnons, is investigated by means of rigorous calculations, correct to arbitrary order in the magneto-optical coupling parameter. It is shown that the concurrent localization of the interacting photon and magnon fields in the same region of space for a long period of time enhances their mutual interaction, provided that specific selection rules are fulfilled. Our results provide evidence for the occurrence of strong effects, beyond the linear response approximation, which lead to enhanced modulation of light by spin waves through multimagnon absorption and emission processes by a photon.